2021
DOI: 10.1055/s-0040-1722277
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regression Modeling for Age Estimation by Assessment and Comparison of Spheno-Occipital Synchondrosis Fusion and Cervical Vertebral Maturation Stages

Abstract: Objectives The aim of this study was (1) to evaluate the relationship between spheno-occipital synchondrosis (SOS) fusion stages, cervical vertebral maturation (CVM) stages, and clivus sizes with chronological age on cone-beam computed tomography (CBCT) images, and (2) to compare these methods for accurate age estimation using regression analysis. Materials and Methods The CBCT images of 200 individuals (102 females and 98 males) were included in the study. The SOS fusion stages and CVM stages were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Belgin et al 3 reported that the age difference between males and females increased gradually into 3.8 years by increase in the SOS fusion stage. However, in the present study, age differences between males and females showed a pattern of increase during the pubertal growth peak (1.5 y in stage 2, 1.8 y in stage 3, and 1.6 y in stage 4) and a decrease upon completion of the pubertal growth spurt (1.3 y in stage 5), which is similar to the results of the CVMI stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Belgin et al 3 reported that the age difference between males and females increased gradually into 3.8 years by increase in the SOS fusion stage. However, in the present study, age differences between males and females showed a pattern of increase during the pubertal growth peak (1.5 y in stage 2, 1.8 y in stage 3, and 1.6 y in stage 4) and a decrease upon completion of the pubertal growth spurt (1.3 y in stage 5), which is similar to the results of the CVMI stage.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The beginning of SOS fusion is known to be related to the start of pubertal growth in adolescents, and its late completion of ossification compared to other synchondroses in the cranial base can allow for the estimation of the skeletal maturation status. 1,[3][4][5][6][7][8][9] Because of the inherent limitations of 2-dimensional lateral cephalograms including the superimposition of adjacent structures, 3-dimensional (3D) computed tomography (CT), including multidetector CT (MDCT) or cone-beam CT (CBCT), has been used to classify the SOS fusion stage according to the radiopacity in SOS with 4-, 5-, or 6-stage scoring methods. 2,3,8,[10][11][12][13] Although SOS fusion is known to occur 1-3 years earlier in females than in males, the exact timing and pattern of SOS fusion are still controversial.…”
Section: Abstract: Cvmi Spheno-occipital Synchondrosismentioning
confidence: 99%
See 2 more Smart Citations